Effect of crop establishment methods on productivity, profitability and energetics of rice (Oryza sativa)-wheat (Triticum aestivum) system - BOHRA, J S; KUMAR, RAKESH (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was carried out from 2007-08 to 2009-10 at Varanasi, Uttar Pradesh to compare the performance of four crop establishment methods (direct dry seeding by zero till drill, direct seeding of sprouted rice seeds in puddled field by drum seeder, hand transplanting and mechanical transplanting through SPT in rice and four tillage methods (rotavator, conventional sowing, strip and zero till drilling) in wheat on productivity, profitability and energetics of rice (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system. Results revealed that hand and mechanical transplanting by SPT of rice (PHB 71) being at par, produced significantly higher grain yield of rice (5.76 and 5.71 tonnes/ha) than direct dry seeding by zero till and direct seeding of sprouted rice by drum seeder under puddled field (3.86 and 4.98 tonnes/ha). However, the use of SPT gave the maximum B:C ratio (2.86) and was significantly superior over hand transplanting (2.58), direct seeding of sprouted rice by drum seeder (2.51) and direct dry seeding by zero till (1.86). In wheat (HD 2733), zero till drill sowing proved most cost effective and recorded markedly higher grain yield (4.05 tonnes/ha), net return (Rupees 44 670/ha ) and B:C ratio (4.19) but statistically at par with conventional sowing than rotavator and strip till. Consequently, among the rice establishment methods hand transplanting produced the maximum system REY (10.2 tonnes/ha/yr) being at par with mechanical transplanting (10.18 tonnes/ha/yr) and both produced significantly higher REY than drum seeder and zero till drill (9.56 and 8.52 tonnes/ha/yr, respectively). In wheat, zero till drill sowing produced the maximum REY (9.92 tonnes/ha/yr) and being comparable to conventional sowing, rotavator and strip till (9.72, 9.52 and 9.30 tonnes/ha/yr, respectively). The similar trend was followed in system productivity of rice and wheat. Moreover, mechanical transplanted rice by SPT (5.62) followed by zero till drill (6.46) sown in wheat gave the highest energy efficiency than other crop establishments methods by ensuring timely and cheap sowing without sacrificing crop yield.